Impact of nerve sparing in robot‐assisted radical prostatectomy on the risk of positive surgical margin and biochemical recurrence. (11th April 2022) - Komori, Hiroki; Blas, Leandro; Shiota, Masaki; Takamatsu, Dai; Matsumoto, Takashi; Lee, Ken; Monji, Keisuke; Kashiwagi, Eiji; Inokuchi, Junichi; Eto, Masatoshi
Abstract : Objectives: Nerve sparing may increase positive surgical margin rate during radical prostatectomy. Our objective was to analyze the positive surgical margin rate and location as well as its impact on biochemical recurrence according to nerve sparing procedure in robot‐assisted radical prostatectomy. Methods: We included 814 patients treated with robot‐assisted radical prostatectomy between 2009 and 2021, and evaluated the impact of nerve sparing on positive surgical margin and biochemical recurrence using logistic regression and Cox models. Results: Unilateral nerve sparing and bilateral nerve sparing were performed in 152 (18.6%) cases and 118 (14.5%) cases, respectively. On multivariable analysis, in addition to nerve sparing, bilateral nerve sparing, but not unilateral nerve sparing was associated with an increased risk of positive surgical margin compared with non‐nerve sparing. Positive surgical margin at any location increased the risk of biochemical recurrence. During unilateral nerve sparing, positive surgical margin in nerve sparing side, but not in non‐nerve sparing side was associated with increased risk of biochemical recurrence on multivariate analysis. Conclusions: Taken together, surgeons need to notice an increased risk of biochemical recurrence associated with positive surgical margin when performing nerve sparing in robot‐assisted radical prostatectomy, and then need to choose the patients suitable for nerve sparing.